2013
DOI: 10.1044/1092-4388(2012/12-0011)
|View full text |Cite
|
Sign up to set email alerts
|

Children's Identification of Consonants in a Speech-Shaped Noise or a Two-Talker Masker

Abstract: Purpose This study evaluated child-adult differences for consonant identification in a noise or a two-talker masker. Error patterns were compared across age and masker type to test the hypothesis that errors with the noise masker reflect limitations in the peripheral encoding of speech, whereas errors with the two-talker masker reflect target-masker confusions within the central auditory system. Method A repeated-measures design compared the performance of children (5–13 years) and adults in continuous speec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
70
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 44 publications
21
70
1
1
Order By: Relevance
“…Large child/adult differences have been observed for closed-set VCV recognition (Leibold and Buss, 2013), open-and closed-set word recognition Corbin et al, 2016;Hall et al, 2002), and sentence recognition (Wightman and Kistler, 2005). Development of speech-in-speech recognition appears to continue into adolescence (Corbin et al, 2016;Wightman and Kistler, 2005).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Large child/adult differences have been observed for closed-set VCV recognition (Leibold and Buss, 2013), open-and closed-set word recognition Corbin et al, 2016;Hall et al, 2002), and sentence recognition (Wightman and Kistler, 2005). Development of speech-in-speech recognition appears to continue into adolescence (Corbin et al, 2016;Wightman and Kistler, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…This type of error is sometimes described as an intrusion from the masker stream. Several studies showing poor speech-in-speech recognition in children have also reported evidence of more intrusions in children's responses (Leibold and Buss, 2013;Wightman and Kistler, 2005), suggesting that their poor performance may be due to a failure of stream segregation and/or a failure to selectively attend to the target stream.…”
Section: Introductionmentioning
confidence: 99%
“…This time course of development appears to extend longer into childhood when the competing background sounds are made up of a small number of competing talkers than when the competing background is steady-state noise (e.g., Bonino et al, 2013; Leibold & Buss, 2013; Wightman & Kistler, 2005). That is, preschoolers and kindergarteners are often more susceptible to interference from complex sounds than older children.…”
Section: Resultsmentioning
confidence: 99%
“…This reduces the resources available for linguistic and cognitive processing and can often result in children 'tuning out' from being overloaded by auditory stimuli [5,38]. Noise levels are reported to be highest in the classrooms of the youngest children [25,33,47,59] which is also the age group most affected [26,32,43,45]. As children's auditory systems are neurologically immature, they have greater perceptual difficulties than adults in discriminating and understanding speech, and cannot use years of previous communicative experience to fill in missing information [58].…”
Section: Introductionmentioning
confidence: 99%